A close examination of speed limit credibility and compliance on UK roads. (April 2020) - Yao, Yao; Carsten, Oliver; Hibberd, Daryl
Abstract: Speed is at the core of the road safety problem and speed management is a tool for road safety. Speed limits that are more credible are supposed to encourage drivers to comply with speed limits, with consequent benefits for road safety. Credible speed limit has been found to be affected by the features of the road surroundings in previous research. This study investigated, by using a questionnaire, whether or not the current legal speed limit is credible on a variety of current UK road environments and what the difference is between the proposed speed limit and the chosen, self-reported driving speed. The survey result revealed that road layout and the roadside environment affected the intrinsic perception of choice of speed and speed limit. Chosen speed limit and proposed speed are not identical but are related with each other. The higher the speed limit drivers perceived, the higher speed they tended to drive. Highlights: Credible speed limits are defined as the speed limit accepted by most drivers without the need of enforcement. Credibility is different to compliance. Road and roadside environment affect speed limit credibility and compliance. Setting credible speed limit will help bring more compliance with speed limit. Speed limit credibility can be achieved by better matching the limit to certain characteristics of the road layout.